You and the natural world the new grade 10 - Religioso, Teresita F.; Vengco, Lilia G.; Navaza, Delia C.; Faraon, Genevieve D. (Quezon City. Phoenix Publishing House, Inc., 2019)
"The accompanying activity manual of You and the Natural World Science K to 12 Second Edition contains experiments designed to explore science through a stimulating yet simple approach to each activity. This edition is designed to introduce and strengthen the students' knowledge, methods, skills, and scientific attitudes while simultaneously recognizing and respecting their educational and development needs".
Includes appendix.
English text.
Keywords: Science